DINAMIKA FISIK PESISIR KAWASAN WISATA PANTAI GUMUMAE KABUPATEN SERAM BAGIAN TIMUR PROVINSI MALUKU - Ilham Marasabessy; Muhammad Iksan Badarudin; Said Alis (JURNAL ENGGANO)
Sebagai salah satu destinasi wisata bahari, pantai Gumumae menjadi lokasi liburan potensial bagi masyarakat Kota Bula dan sekitarnya. Memiliki luas 19.70 ha membantang dari Teluk Sesar sampai Sungai Wailola, turut berkontribusi pada pembentukan struktur dan karakteristik pantai. Dinamika fisik pesisir yang kompleks menjadi tujuan penelitian dilakukan. Harapannya pengelolaan Pantai Gumumae sebagai kawasan wisata bahari dapat dilakukan secara tepat dan berkelanjutan. Penelitian dilakukan pada bulan September sampai Oktober 2019, di Pantai Gumumae Kabupaten Seram Bagian Timur Provinsi Maluku. Pengamatan parameter fisik pesisir dilakukan secara insitu dan komparasi data penginderaan jauh, melalui satelit altimetri NASATOPEX/Poseidon, Jason-1/Envisat, dan Jason-2/Envisat tanggal 2 - 17 September 2019. Menggunakan analisis deskriptif kuantitatif, spasial dan temporal melalui citra satelit Landsat 8 dan arcgis imagery 2019, untuk mengetahui pengaruh dinamika fisik dalam bentuk peta tematik. Pantai Gumumae merupakan dataran rendah tetapi dikelilingi wilayah perbukitan disekitarnya. Pola curah hujan berfluktuasi dalam setahun, namun terdapat trend peningkatan sejak bulan September sampai November dan berdampak pada aliran sungai, tidak mengherankan transport sedimen yang dialirkan ke pesisir pantai Gumumae melalui muara sungai Wailola berada dalam jumlah yang besar. Termasuk kategori perairan dangkal dengan kedalaman 45 cm sampai 2.5 meter pada jarak >15 meter dari garis pantai ke arah laut. Tinggi gelombang relatif kecil yakni sebesar 0.68 meter – 0.82 meter, namun memiliki arus yang cenderung cepat di muara sungai Wailola. Anomali permukaan laut di pesisir Gumumae mengalami penurunan secara konstan sebesar 3mm sampai 116 mm. Kecepatan arus dan sudut elevasi perairan pantai mengalami fluktuasi sehingga memberi pengaruh pada arah dan kekuatan arus pantai, gelombang kecil, sedimentasi tinggi di muara hingga sebagian kawasan wisata. Perlu perencanaan yang komprehensif untuk pengelolaan wisata pantai Gumumae berdasarkan kesesuaian tata ruang. As one of the marine tourism destinations, Gumumae beach is a potential vacation area for the people of the city of Bula and its surroundings. It has an area of 19.70 ha stretching from the Sesar bay to the Wailola river, contributing to the formation of the structure and characteristics of the coastal. The complex physical dynamics of the coastal is the aim of the study. It is hoped that the management of Gumumae beach as a marine tourism area can be carried out appropriately and sustainably. The study was conducted from September to October 2019, on the coastal of Gumumae, East Seram Regency, Maluku Province. Observation of coastal physical parameters was carried out insitu and compared remote sensing data, via satellite altimetry NASATOPEX / Poseidon, Jason-1 / Envisat, and Jason-2 / Envisat on 2-17 September 2019. Using quantitative descriptive analysis, spatial and temporal through satellite imagery. Landsat 8 and Arcgis Imagery 2019, to determine the effect of the physical dynamics of the Gumumae coastline in the form of thematic maps. Gumumae Beach is a low-lying area but is surrounded by hilly areas around it. Rainfall patterns fluctuate within a year, but there is a trand increase from September to November and have an impact on river flow, it is not surprising that sediment transport flowed to the coastal of Gumumae via the Wailola river mouth is in large numbers. Current velocity and elevation angle of coastal waters fluctuate so that it influences the direction and strength of coastal currents. Included in the category of shallow water with a depth of 45 cm to 2.5 meters at a distance of> 15 meters from the coastline towards the sea. The wave height is relatively small at 0.68 meters - 0.82 meters, but has a current that tends to be fast at the mouth of the Wailola river. Sea level anomalies on the coastal of Gumumae are constantly decreasing by 3mm to 116 mm. Need a comprehensive planning for the management of Gumumae beach tourism based on spatial suitability. As one of the marine tourism destinations, Gumumae beach is a potential vacation area for the people of the city of Bula and its surroundings. It has an area of 19.70 ha stretching from the Sesar bay to the Wailola river, contributing to the formation of the structure and characteristics of the coastal. The complex physical dynamics of the coastal is the aim of the study. It is hoped that the management of Gumumae beach as a marine tourism area can be carried out appropriately and sustainably. The study was conducted from September to October 2019, on the coastal of Gumumae, East Seram Regency, Maluku Province. Observation of coastal physical parameters was carried out insitu and compared remote sensing data, via satellite altimetry NASATOPEX / Poseidon, Jason-1 / Envisat, and Jason-2 / Envisat on 2-17 September 2019. Using quantitative descriptive analysis, spatial and temporal through satellite imagery. Landsat 8 and Arcgis Imagery 2019, to determine the effect of the physical dynamics of the Gumumae coastline in the form of thematic maps. Gumumae Beach is a low-lying area but is surrounded by hilly areas around it. Rainfall patterns fluctuate within a year, but there is a trand increase from September to November and have an impact on river flow, it is not surprising that sediment transport flowed to the coastal of Gumumae via the Wailola river mouth is in large numbers. Current velocity and elevation angle of coastal waters fluctuate so that it influences the direction and strength of coastal currents. Included in the category of shallow water with a depth of 45 cm to 2.5 meters at a distance of> 15 meters from the coastline towards the sea. The wave height is relatively small at 0.68 meters - 0.82 meters, but has a current that tends to be fast at the mouth of the Wailola river. Sea level anomalies on the coastal of Gumumae are constantly decreasing by 3mm to 116 mm. Need a comprehensive planning for the management of Gumumae beach tourism based on spatial suitability.